Spermine-Mediated Tolerance to Selenium Toxicity in Wheat (Triticum aestivum L.) Depends on Endogenous Nitric Oxide Synthesis - Md. Mahadi Hasan; Basmah M. Alharbi; Haifa Abdulaziz Sakit Alhaithloul; Awatif M. Abdulmajeed; Suliman Mohammed Alghanem; Amina A. M. Al-Mushhin; Mohammad Shah Jahan; Francisco J. Corpas; Xiang-Wen Fang; Mona H. Soliman (MDPI AG, 2021)
Excess selenium (Se) causes toxicity, and nitric oxide (NO)'s function in spermine (Spm)-induced tolerance to Se stress is unknown. Using wheat plants exposed to 1 mM sodium selenate-alone or in combination with either 1 mM Spm, 0.1 mM NO donor sodium nitroprusside (SNP) or 0.1 mM NO scavenger cPTIO-the potential beneficial effects of these compounds to palliate Se-induced stress were evaluated at physiological, biochemical and molecular levels. Se-treated plants accumulated Se in their roots (92%) and leaves (95%) more than control plants. Furthermore, Se diminished plant growth, photosynthetic traits and the relative water content and increased the levels of malondialdehyde, H2O2, osmolyte and endogenous NO. Exogenous Spm significantly decreased the levels of malondialdehyde by 28%, H2O2 by 37% and electrolyte leakage by 42%. Combined Spm/NO treatment reduced the Se content and triggered plant growth, photosynthetic traits, antioxidant enzymes and glyoxalase systems. Spm/NO also upregulated MTP1, MTPC3 and HSP70 and downregulated TaPCS1 and NRAMP1 (metal stress-related genes involved in selenium uptake, translocation and detoxification). However, the positive effects of Spm on Se-stressed plants were eliminated by the NO scavenger. Accordingly, data support the notion that Spm palliates selenium-induced oxidative stress since the induced NO elicits antioxidant defence upregulation but downregulates Se uptake and translocation. These findings pave the way for potential biotechnological approaches to supporting sustainable wheat crop production in selenium-contaminated areas.